2015
DOI: 10.1080/14999013.2014.974088
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Mental Disorder and Recidivism in Sexual Offenders

Abstract: The importance of mental illness as a risk factor for violence has been debated with significant implications for mental health policy and clinical practice. In offender samples, mental health diagnoses tend to be unrelated to recidivism, although this effect has been questioned recently in sexual offenders. In the present, prospective investigation, the relevance of several mental health diagnoses and relevant co-morbidity is examined as predictors of various types of recidivism in two distinct samples of sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 35 publications
5
22
0
Order By: Relevance
“…Consistent with the results of the most recent meta-analyses (Bonta, Blais, & Wilson, 2014) and subsequent studies (Kingston et al, 2015;Rezansoff et al, 2013), the best predictors of criminal recidivism were consistent with the central eight risk factors identified within the GPCSL.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Consistent with the results of the most recent meta-analyses (Bonta, Blais, & Wilson, 2014) and subsequent studies (Kingston et al, 2015;Rezansoff et al, 2013), the best predictors of criminal recidivism were consistent with the central eight risk factors identified within the GPCSL.…”
Section: Discussionsupporting
confidence: 84%
“…In an updated meta-analysis, Bonta, Blais, and Wilson (2013) reported that the central eight risk factors were important predictors of general and violent recidivism among mentally disordered offenders, whereas clinical variables, such as schizophrenia were not significant predictors. Since the publication of this latest quantitative review, several studies have been conducted that continue to support the notion that mental illness fails to reliably predict recidivism in offender samples and that the best predictors are consistent with the GPCSL model (Kingston, Olver, Harris, Wong, & Bradford, 2015;Rezansoff, Moniruzzaman, Gress, & Somers, 2013;Skeem, Winter, Kennealy, Louden, & Tatar, 2014).…”
Section: Relationship Between Mental Illness and Violencementioning
confidence: 82%
“…Of those diagnoses, only exhibitionistic disorder predicted sexual reoffending while a history of alcohol misuse predicted any new prison term or psychiatric placement. These findings corroborate the marginal associations found elsewhere between categorial diagnoses and reoffense in sexual offenders (4). Furthermore, the criminological variables of the Static-99, usually robustly linked to reoffense, did not significantly predict either recidivism outcome in our sample.…”
Section: Discussionsupporting
confidence: 90%
“…Although empirical findings support the association between increased offending in general and diagnoses such as schizophrenia or affective illness, particularly when mediated by substance misuse (2), the extant literature has not demonstrated a robust association between a major mental illness per se and sexual offending (3). The existing literature has demonstrated sexual violence to be associated with learning disabilities, substance abuse, personality disorders, and sexual disorders (4,5). Indeed, research has demonstrated that up to 90% of incarcerated sexual offenders have at least one psychiatric disorder (for more details see 6).…”
Section: Introductionmentioning
confidence: 96%
“…This follows on from several studies that have shown that some mental disorders have a higher than chance association with violent offending (e.g., Brennan, Mednick, & Hodgins, ) and should be considered as risk factors (Douglas, Guy, & Hart, ; Hodgins, ). In samples drawn from the criminal justice system, however, mental disorder or its symptoms have not generally been implicated in recidivism, or only weakly so (Bonta, Blais, & Wilson, ; Kingston et al, ; Kingston, Olver, Harris, Wong, & Bradford, ; Rezansoff, Moniruzzaman, Gress, & Somers, ; Skeem, Winter, Kennealy, Louden, & Tatar II, ). In such studies, however, the role of treatment is rarely explored, with Keers, Ullrich, DeStavola, and Coid () a notable exception.…”
Section: Introductionmentioning
confidence: 99%